Wireless Network Security Using Hotspot Login Authentication Method: Keamanan Jaringan Nirkabel Menggunakan Metode Otentikasi Masuk Hotspot - Bima Yusup Septiana; Yogi Irdes Putra; Fitri Yanti (Academia Open, 2025)
Abstract. General Background: Wireless networks are widely used in public spaces such as cafés, yet their openness often poses risks of security breaches, uncontrolled bandwidth usage, and poor service quality. Specific Background: At Café Lilnook Karawaci, Tangerang, the Wi-Fi network lacked authentication, user restrictions, and bandwidth management, making it vulnerable to misuse and inefficiency. Knowledge Gap: While prior studies emphasize the importance of network authentication and monitoring, limited research explores practical hotspot login authentication using MikroTik RouterBoard in small business environments. Aims: This study aims to design, implement, and evaluate a secure wireless network system with hotspot login authentication using MikroTik RB50UG, guided by the Network Development Life Cycle (NDLC) method. Results: Functionality testing with five users and two administrators achieved a feasibility score of 1 (feasible), while usability testing reached 100% (very feasible), confirming effectiveness in both security and performance management. Novelty: The research integrates captive portal-based hotspot authentication with customized configurations in a café setting, demonstrating an adaptable and cost-effective approach to small-scale network security. Implications: Findings indicate that implementing hotspot login authentication not only enhances security and service quality but also provides a scalable model for similar public access networks, supporting safer digital environments in hospitality sectors.Highlight : Hotspot login authentication enhances network security in public environments. Functionality and usability tests show the system is feasible and effective. Applying the NDLC method provides a structured process from design to network management. Keywords : Authentication, Login Hotspot, NDLC, Functionality, Usability